3D Model Autocad Of The Piston Displacer Cup For A Gamma Stirling Engine Using The API Method - Rahmat, Rahmat; Dean Anggara Putra; Rifo Nurlaksana Restu; Jefri Imron; Marhaendra Natawibawa; Hery Sumardiyanto; Khairil Munawar; Thomas Junaedi (STEKOM PRESS, 2025)
When producing a perfect product, design process namely 2D modeling and 3D drawing, are closely related. The purpose of this study is to design a 3D model of a gun mastering machine product as a fan drive using CAD applications. The method of this study is decision data on API production (analytical product inspection). Measurement of sterling machine degradation using CPK (deviation) received results of -0.97, -0.22, 0.86, 0.11, 0.11 between zero and what indicates this specification. On average, the results of the stirling fluid fluorescent agent measurement are red numbers indicating that the survey dimensions are absent, especially from the basic dimensions of point 4, with samples 2, 3, and 5 exceeding the specified tolerance limits.